PWE-099 Porto-systemic shunt embolization and recurrent ascites: a single centre case series. (22nd June 2015) - Figorilli, F; Mehta, G; MacNaughtan, J; Patch, D; Yu, D; Jalan, R
Abstract : Introduction: Porto-systemic shunt embolization (PSSe) is an emerging procedure for the treatment of refractory hepatic encephalopathy (HE). 1 A criteria of MELD <11 was proposed by Laleman et al as a cutodd to predict recurrent HE post embolization. No other significant liver-related complications were noted in this retrospective study. The aim of this retrospective study was to assess the efficacy and complication rate following PSSe at a single institution. Method: All cirrhotic patients undergoing PSSe for refractory HE between March 2008 – September 2014 at Royal Free London were included in this study. Cirrhotic patients had refractory HE (West Haven score ≥2), an EEG pattern consistent with HE, and a demonstrable PSS on CT/MRI. All patients underwent embolization using Amplatz vascular plugs. Clinical and biochemical variables at the time of PSSe were recorded, and outcomes including HE grade, changes in MELD score and portal hypertension-related complications were noted. Results: Ten patients underwent PSSe (M: 6; Age 60.9 ± 10.3 yr) and mean follow up was 37.3 ± 59.6 mo. A baseline MELD score >11 was present in 5 patients. No significant change in mean MELD score was seen following PSSe (11.5 ± 2.8 vs 12.2 ± 6.9, pre vs post p = 0.57). No patients experienced variceal haemorrhage post PSSe. Five patients had diuretic controlled ascites prior to PSSe. Following PSSe two patients developed severe ascites requiring large volume paracentesis (Table 1 ). HE improved in 6 patients; recurrent HE developed in 4 patients – grade 3 in 2 patients, and grade 4 in 2 patients (Table 1 ). MELD >11 did not predict occurence of ascites or HE post PSSe. Conclusion: This small retrospective series demonstrates a 20% incidence of severe ascites post PSSe. With the caveat of the small size of this cohort, MELD score did not predict ascites or HE following PSSe. Further assessment of degree of portal hypertension, or of porto-systemic shunting, through hepatic haemodynamic and ICG studies may better predict the development of complications and the necessity for a concomitant TIPS at the time of PSSe. Disclosure of interest: None Declared. Reference: Laleman W, et al . Embolization of large spontaneous portosystemic shunts for refractory hepatic encephalopathy: a multicenter survey on safety and efficacy. Hepatology 2013;57:2448–2457